(untitled) (Cultura Económica, 2019)
The northwest of Argentina (NOA) is a region of the country that, throughout the years, has not defined a local identity. Its culture is the result of the superposition and the movement of the different groups of inhabitants that have lived in the territory. Therefore, the NOA presents itself as a space defined by diversity. Gaspar Risco, a recognized intellectual from Tucumán, explains that the different cultures occupied the territory by means of juxtaposition and not through dialogue with the preceding culture. The article also considers the interaction that the NOA has had with the rest of the country. Finally, the author calls upon a transformation of this region, oriented to the conformation of a unifying “us”, as a result of intercultural dialogue.